Concept of minimizing the response time for reducing dynamic data redundancy in cloud computing - Wan Nurazieelin Wan Abd Manan; Mohamad Aizi Salamat (Institute of Advanced Engineering and Science, 2019)
Reduction of dynamic data redundancy in cloud computing is one of the best ways to maintain the storage capacity from being fully utilized. Cloud storage is a part of cloud computing technology which holds a high demand in any organization for reducing the cost of purchasing and maintaining storage infrastructures. Increase in the number of users will require a larger storage capacity for storing their data. Reduction of dynamic data redundancy allows service providers to be energy savvy and minimize maintenance cost. Recent researches focus more on static data nature despite its limited capability as compared to dynamic data characteristic in cloud storage. Therefore, this paper theoretically compares various techniques for reduction of redundant dynamic data in cloud computing and suggests the best technique for completing the task in terms of response time.